The Effects of E-Trust and E-Service Quality to E-Loyalty with E-Satisfaction as the Mediation Variable (The Study of Bebas Bayar Application User’s in Indonesian) - Gotama, Febrianto; Indarwati, Tias Andarini (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2019)
This research aims to examine the effect of e-trust and e-service quality on e-loyalty of Bebas Bayar application with e-satisfaction as a mediation variable. This study used a non-probability sampling of 220 respondents and path-analysis. The results of this study show that all proposed variable hypotheses are significant, but e-service quality has no significant influence on e-loyalty. E-trust and e-service quality have a significant effect on e-loyalty with e-satisfaction as a mediation variable.